Text Comprehension and Study Method Acquisition for Students with Specific Learning Disorder: Development and First Application of the SUST Program - Rizzo, Amalia Lavinia; Traversetti, Marianna (Science Insights Education Frontiers, 2021)
In this paper we describe an educational program for the development of the study method for students with specific learning disorders (SLD) and a first Italian application on a small sample of fifth grade students. This experience was aimed at collecting useful data precisely to review and improve the above-mentioned program. A particularly relevant problem was identified looking at the anthropological dimension of the capability learning and the need for students to acquire the learning to learn ability. Specifically, it is about the low levels of text comprehension in Italian schools and its consequences on the study activities. Within the inclusive perspective and taking into account the effective didactic strategies in the evidence-based education (EBE) perspective, the project created and tested a teaching kit (SUST) for the fifth classes of the primary school, at-tended by students with SLD. This experimental framework was conducted following the Design Based Research methodology. It also focused on the training of teachers within the intervention classes. The positive results of SUST application open a constructive scenario for the definition of intervention programs aimed at improving text comprehension and study skills of students with SLD. This program should be tested in a wider context of schools.